Determinación de la correlación estadística entre las variables del comportamiento organizacional en la empresa REYVER S.A. - Ormaza Ostaíza, Jaime Andrés (2017)
The determination of the statistical correlation between the variables of organizational behavior with the highest incidence in the dairy company REYVER SA was focused on evaluating the performance and the organizational environment, for this in the first instance proceeded to the development of the Method of Experts with a Group formed by 9 professionals, from which 7 were selected because of the high degree of knowledge and involvement towards the subject, later, from a list and with the help of the methodology KENDALL & KENDALL provided the most significant variables for achievement Of the objectives, the manager of the company was interviewed, who provided information concerning the operation of the organization and mentioned the different factors of convergence during the working day and the development of the activities of each employee. On the other hand, the survey revealed a lack of approximation to higher hierarchical levels, the lack of adequate means of communication and the absence of organizational objectives, on the basis of which a plan of actions was managed to manage each One of the adverse situations to improve the quality of working life and productivity of the organization.